2008
DOI: 10.1007/s11109-008-9074-9
|View full text |Cite
|
Sign up to set email alerts
|

Shot by the Messenger: Partisan Cues and Public Opinion Regarding National Security and War

Abstract: Research has shown that messages of intra-party harmony tend to be ignored by the news media, while internal disputes, especially within the governing party, generally receive prominent coverage. We examine how messages of party conflict and cooperation affect public opinion regarding national security, as well as whether and how the reputations of media outlets matter. We develop a typology of partisan messages in the news, determining their likely effects based on the characteristics of the speaker, listener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 32 publications
5
95
0
Order By: Relevance
“…By contrast, for non-conservatives, agreement went from 22% to 13% (n = 97). 22 More generally, Hartman and Weber (2009) and Baum and Groeling (2009) find that messages from sources that match a subject's ideological or partisan affiliation are more persuasive than those that do not.…”
Section: Study 2: Spring 2006mentioning
confidence: 99%
“…By contrast, for non-conservatives, agreement went from 22% to 13% (n = 97). 22 More generally, Hartman and Weber (2009) and Baum and Groeling (2009) find that messages from sources that match a subject's ideological or partisan affiliation are more persuasive than those that do not.…”
Section: Study 2: Spring 2006mentioning
confidence: 99%
“…Further, several researchers explain causal inferences in terms of expectancies (Baum and Groeling, 2009;Eagly and Chaiken, 1975;Eagly et al, 1978;Vermeulen and Seegers, 2009;Wood and Eagly, 1981). Specifically, it has been suggested that, the more a communicator's position advocated in the persuasive message is expected based on the communicator's dispositional characteristics, the more recipients of the message will discount factual evidence as a plausible cause, and the less persuasive will be the message.…”
Section: H1mentioning
confidence: 99%
“…See also Lacina and Lee (2012), who examine how regime type affects perceptions of threat, and Geva and Hanson (1999), who focus on sociocultural similarity. 2 For other recent examples of experiments about international security, see Herrmann, Tetlock, and Visser (1999); Herrmann and Shannon (2001); Berinsky (2007; ;Gartner (2008); Baum and Groeling (2009) ;Gelpi, Feaver, and Reifler (2009) ;Grieco et al (2011); Horowitz and Levendusky (2011);McDermott (2011); Tingley (2011); Tingley and Walter (2011);Tomz (2007); Trager and Vavreck (2011); Levendusky and Horowitz (2012), and Press, Sagan, and Valentino (2013). hypothesis that the preferences of ordinary voters contribute to peace among democracies.…”
mentioning
confidence: 99%